2022
DOI: 10.3389/fendo.2022.956169
|View full text |Cite
|
Sign up to set email alerts
|

Female fertility does not require Bmal1 in suprachiasmatic nucleus neurons expressing arginine vasopressin, vasoactive intestinal peptide, or neuromedin-S

Abstract: Disruptions to the circadian system alter reproductive capacity, particularly in females. Mice lacking the core circadian clock gene, Bmal1, are infertile and have evidence of neuroendocrine disruption including the absence of the preovulatory luteinizing hormone (LH) surge and enhanced responsiveness to exogenous kisspeptin. Here, we explore the role of Bmal1 in suprachiasmatic nucleus (SCN) neuron populations known to project to the neuroendocrine axis. We generated four mouse lines using Cre/Lox technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…However, the same mice exhibit more severe disturbance of wheel-running behavior rhythm resembling those described as “arrhythmic” or “split” in VPAC2 neuron-specific Bmal1 deletion ( 25 ). In addition, impaired circadian rhythms of home-cage activity and body temperature in Avp-Bmall -/- mice are strikingly similar to those of Nms-Bmal1 -/- mice ( 35 ). The latter has been reported to be arrhythmic in wheelrunning rhythm ( 34 ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the same mice exhibit more severe disturbance of wheel-running behavior rhythm resembling those described as “arrhythmic” or “split” in VPAC2 neuron-specific Bmal1 deletion ( 25 ). In addition, impaired circadian rhythms of home-cage activity and body temperature in Avp-Bmall -/- mice are strikingly similar to those of Nms-Bmal1 -/- mice ( 35 ). The latter has been reported to be arrhythmic in wheelrunning rhythm ( 34 ).…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, Lee et al reported that mice with Bmal1 deletion in NMS neurons ( Nms-Bmal1 -/- mice) were arrhythmic in wheel-running behavior ( 34 ). Notably, a recent study showed that rhythms of home-cage activity and body temperature in Avp-Bmal1 -/- mice were very similar to those in Nms-Bmal1 -/- mice ( 35 ). Given the critical role of SCN AVP neurons in setting the free-running period, we re-evaluated the circadian behavior rhythm of Avp-Bmal1 -/- and Avp-CK1δ -/- mice by measuring wheel-running activity.…”
Section: Resultsmentioning
confidence: 90%
“…In contrast, Lee and colleagues reported that mice with Bmal1 deletion in NMS neurons ( Nms-Bmal1 −/− mice) lost the circadian rhythm in wheel-running behavior [ 21 ]. Notably, a recent study showed that rhythms of home-cage activity and body temperature in Avp-Bmal1 −/− mice were very similar to those in Nms-Bmal1 −/− mice [ 34 ]. Thus, circadian phenotypes may be significantly different between wheel-running and home-cage activity rhythms.…”
Section: Resultsmentioning
confidence: 99%